Familiarization Protocol Influences Reproducibility of 20-km Cycling Time-Trial Performance in Novice Participants - Hibbert, Andrew W.; Billaut, François; Varley, Matthew C.; Polman, Remco C. J. (Frontiers in Physiology, 2017)
Introduction: Exercise performance is reproducible in experienced athletes; however, less trained participants exhibit greater variability in performance and pacing. To reduce variability, it is common practice to complete a familiarization prior to experimental testing. However, there are no clear guidelines for familiarizing novice participants to a cycling time-trial (TT), and research findings from novice populations may still be influenced by learning effects. Accordingly, the aims of this study were to establish the variability between TTs after administering differing familiarization protocols (duration or type) and to establish the number of familiarization trials required to limit variability over multiple trials. Methods: Thirty recreationally active participants, with no prior experience of a TT, performed a 20-km cycling TT on five separate occasions, after completing either a full (FF, 20-km TT, n=10), a half (HF, 10-km TT, n=10) or an equipment familiarization (EF, 5-min cycling, n=10). Results: Variability of TT duration across five TTs was the lowest after completing FF (P = 0.69, ηp2 = 0.05) compared to HF (P = 0.08, ηp2 = 0.26) and EF (P = 0.07, ηp2 = 0.21). In the FF group after TT2, the effect size for changes in TT duration was small (d < 0.49). There were large differences between later TTs in HF (d = 1.02, TT3-TT4) and EF (d = 1.12, TT4-TT5). The variability in mean power output profiles between trials was lowest within FF, with a similar pacing profile reproduced between TT3-TT5. Discussion: Familiarization of the exercise protocol influenced reproducibility of pacing and performance over multiple, maximal TTs, with best results obtained after a full experience of the exercise compared to HF and EF. The difference of TT1 to later TTs indicates that one familiarization is not adequate in reducing the variability of performance for novice participants. After the FF and an additional TT, performance changes between TTs were small, however, a reproducible pacing profile was not developed until after the FF and two additional TTs. These findings indicate that a minimum of three full familiarizations are necessary for novice participants to limit systematic error before experimental testing.